Correlation Between Memory An Qur'an With Student Learning Achievement At Ash-Shohwah Integrated Islamic Junior High School, Berau- East Kalimantan - Nurul Hidayah; Tobroni Tobroni; Achmad Tito Rusady (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This study aims to describe whether there is a correlation between the memorization of the Qur'an and student achievement and the form of the correlation between the ability to memorize the Qur'an and learning achievement. This research uses a mixed approach (mixed methods) with a sequential explanatory research type. Data in this study were obtained through observation, interviews, questionnaires, and documentation. quantitative and qualitative data analysis was carried out by comparing the quantitative data carried out in the first stage and the qualitative data in the second stage. The study results show that: (1) There is a significant correlation or correlation between the memorization of the Qur'an and student achievement at SMPIT Ash-Sohwa Berau. (2) The correlation between memorizing the Qur'an and learning achievement is when a person memorizes the Qur'an, his brain is accustomed to remembering and storing the verses of the Qur'an, which requires a high level of focus and accuracy. So that the brain gets used to being focused and thorough, which positively impacts other activities, including the learning process at school. In addition, those who memorize al-Qur’an are given the ease in life by Allah ﷻ and are directly guided in living life so that they are protected from things that are not good.